How does the development of rural broadband in China affect agricultural total factor productivity? Evidence from agriculture-related loans - Li, Ying (Frontiers in Sustainable Food Systems, 2024)
Introduction The construction of digital villages is widely acknowledged as a way to achieve the “dual goals” of high quality of the agricultural and rural economy and common prosperity under the digital China strategy. Studies have explored the socio-economic benefits of different aspects of rural digitization, but few have focused on the productivity role of rural broadband development in the context of the urban-rural broadband divide. The purpose of this paper is to explore the relationship between rural broadband development and agricultural total factor productivity (TFP) and the intrinsic mechanism of action, and to provide empirical evidence on the productivity effect of promoting digital transformation in rural agriculture. Methods Using panel data from 31 provinces in China from 2011 to 2020, this paper investigates the impact and mechanism of rural broadband development on agricultural TFP from the perspective of agriculture-related loans by setting up a two-way fixed effects model, a mechanism effects model and a threshold effects model. Results The results find that rural broadband development has a significant role in enhancing agricultural TFP. Heterogeneity analysis indicates that the productivity-enhancing effect of rural broadband development is remarkable only in the central region and the region with higher rural disposable income. Mechanism analysis points out that rural broadband development can increase agricultural TFP by influencing the share of farm-related loans. Threshold analysis further reveals that the role of increasing the share of farm-related loans on agricultural TFP is marked only after rural broadband development reaches a certain level. Discussion These findings can provide practical guidance for other developing countries in accelerating the digital transformation of villages and optimizing factor allocation to achieve high-quality agricultural development.